Synthesis of zinc oxide nanoparticles using Trichoderma harzianum and its bio-efficacy on Alternaria brassicae - Mishra, Deep Narayan; Prasad, Lakshman; Suyal, Usha (Frontiers in Microbiology, 2025)
Increasing concerns about chemical fungicides require sustainable alternatives for crop protection. Microbe-mediated synthesis of metal nanoparticles offers a sustainable, eco-friendly and highly effective strategy for plant disease management. This study investigates the mycosynthesis of zinc oxide nanoparticles (ZnO NPs) using the culture filtrate of Trichoderma harzianum and their antifungal activity against Alternaria brassicae. Nanoparticles were synthesized under optimized conditions of cell-free culture filtrate (CFCF) concentration, substrate concentration, pH and temperature. Ultraviolet-visible (UV-Vis) spectroscopy confirmed an absorption peak between 200 and 400 nm, while X-ray diffraction (XRD) confirms the hexagonal crystal structure with an average size of 29 nm. Dynamic light scattering (DLS) and zeta potential analysis revealed a hydrodynamic size of 50.79 nm and a surface charge of −17.49 mV, indicating good stability. Fourier transform infrared (FTIR) spectroscopy analysis identified functional groups (C=O, N-O, and O-H) that are crucial for nanoparticles stabilization. Scanning electron microscopy (SEM) and High-resolution transmission electron microscopy (HR-TEM) analysis revealed spherical, rod-shaped and hexagonal nanoparticles with sizes between 12 and 41 nm. Mycogenic-zinc oxide nanoparticles (M-ZnO NPs) significantly inhibited the mycelial growth of A. brassicae by 91.48% at 200 μg/mL, compared to chemically synthesized ZnO NPs at 200 μg/mL (79.62%) and mancozeb 0.2% (82.96%). SEM-EDX analysis revealed deformations and absorption of M-ZnO NPs in fungal hyphae, while confocal laser scanning microscopy (CLSM) showed increased reactive oxygen species (ROS) formation and impaired membrane integrity in treated fungal cells. Stress enzyme analysis confirmed increased superoxide dismutase (SOD) and catalase (CAT) activity by 44.2 U/mol and 39.6 U/mol at 200 μg/mL M-ZnO NPs. Our studies suggest that the M-ZnO NPs synthesized with T. harzianum culture filtrate have increased antifungal activity even at lower doses and can be used as an alternative to traditional fungicides without affecting environment.